PELATIHAN PENGGUNAAN KOMPONEN DIODA PADA RANGKAIAN ELEKTRONIKA BAGI MAHASISWA FAKULTAS ILMU KOMPUTER UNIVERSITAS LANCANG KUNING PEKANBARU - Atmam Atmam; Zulfahri Zulfahri; Usaha Situmeang (Universitas Lancang Kuning, 2018)
Abstract Faculty of Computer Science is one of the Faculty of the University of Lancang Kuning Pekanbaru, consists of 2 (two) study programs namely Information Systems and Informatics Engineering. Electronic Physics and Advanced Electronics is a compulsory subject for the students of Informatics Engineering Faculty of Computer Science. This course provides an understanding of electronics components. Theoretically, Informatics Engineering students have obtained material about the electronic component. However, the mastery of electronics is not separated by the process of practicum. The problem that occurs is the lack of mastery of electronics in practice. Currently, the practicum process has not been implemented and has an impact on the lack of students' ability in terms of electronics practice. Seeing these conditions then there should be efforts to equip students in the Information Engineering practically in the use of electronic components. One of the knowledge and skills is the use of electronics components in simple circuit is through the training of diode usage in rectifier circuit. The result of this community service activity is the participants' knowledge about electronic defenisi, 100% of participants already know it with 8% increase and the knowledge of electronic component from participant is increase 24%. The participants' knowledge about the use of diodes in the rectifier circuit is 72% and the participants already know the technique of electronic component soldering which is initially 24% and an increase of 76%. Keywords— Electronics, diode, rectifier Abstrak Fakultas Ilmu Komputer adalah salah satu Fakultas di Universitas Lancang Kuning Pekanbaru, terdiri dari 2 (dua) program studi yaitu Sistem Informasi dan Teknik Informatika. Fisika Elektronika dan Elektronika Lanjut adalah mata kuliah wajib bagi mahasiswa Teknik Informatika Fakultas Ilmu Komputer. Mata kuliah ini memberikan pemahaman tentang komponen elektronika. Secara teoritis mahasiswa Teknik Informatika telah memperoleh materi tentang komponen elektronika tersebut. Namun, penguasaan ilmu elektronika ini tidak terlepas dengan adanya proses praktikum. Permasalahan yang terjadi adalah kurangnya penguasaan ilmu elektronika secara praktek. Saat ini, proses praktikum belum dilaksanakan dan berdampak kepada kurangnya kemampuan mahasiswa dari segi praktek elektronika. Melihat kondisi tersebut maka haruslah ada upaya untuk membekali mahasiswa Teknik Informatika secara praktis dalam penggunaan komponen elektronika. Salah satu pengetahuan dan keterampilan adalah penggunaan komponen elektronika pada rangkaian sederhana adalah melalui pemberian pelatihan penggunaan dioda pada rangkaian penyearah. Hasil Kegiatan pengabdian kepada masyarakat ini adalah pengetahuan peserta tentang defenisi elektronika, 100% peserta sudah mengetahuinya dengan peningkatan sebesar 8% serta pengetahuan komponen elektronika dari peserta terjadi peningkatan sebesar 24%. Peningkatan pengetahuan peserta tentang penggunaan dioda pada rangkaian penyearah sebesar 72% dan peserta sudah mengetahui teknik penyolderan komponen elektronika dimana awalnya 24% dan terjadi peningkatan sebesar 76%. Kata kunci— Elektronika, Dioda, Penyearah